Inhibition of 5α-reductase, IL-6 secretion, and oxidation process of equisetum debile roxb. Ex vaucher extract as functional food and nutraceuticals ingredients - Wantida Chaiyana (2018)
© 2017 by the authors. Licensee MDPI, Basel, Switzerland. This study aims to investigate the biological activities related to hair loss of Equisetum debile extracts, including 5α-reductase inhibition, interleukin-6 (IL-6) secretion reduction, and anti-oxidation. E. debile extracts were obtained by maceration in various solvents. Crude extract (CE) was obtained by maceration in 95% ethanol. Chlorophyll-free extract (CF) was the CE which of the chlorophyll has been removed by electrocoagulation. Hexane extract (HE), ethyl acetate extract (EA), and ethanolic extract (ET) were fraction extracts obtained from maceration in hexane, ethyl acetate, and 95% ethanol, respectively. The extracts were investigated for inhibitory activity against 5α-reductase and IL-6 secretion. Total phenolic contents (TPC) were investigated and antioxidant activities were determined by means of 2,20-azino-bis-3-ethylbenzothiazoline-6-sulfonic acid (ABTS), 2,20-diphenyl-1-picrylhydrazyl (DPPH), and ferric reducing antioxidant power (FRAP) assays. The inhibition of lipid peroxidation was determined by the ferric thiocyanate method. The cytotoxicity of the extracts on dermal papilla cells and irritation test by hen's egg test chorioallantoic membrane assay were also investigated. All extracts could inhibit 5α-reductase and decrease IL-6 secretion in lipopolysaccharide-stimulated macrophage. The antioxidant activity of E. debile extracts was directly related to their TPC. ET which contained the highest TPC (68.8 ± 6.7 mg GA/g) showed the highest equivalent concentration (EC1) of 289.1 ± 26.4 mM FeSO4/g, TEAC of 156.6 ± 34.6 mM Trolox/g, and 20.0 ± 6.0% DPPH inhibition. However, EA exhibited the highest inhibition against lipid peroxidation (57.2 ± 0.4%). In addition, EA showed no cytotoxicity on dermal papilla cell line and no irritation on chorioallantoic membrane of hen’s eggs. In conclusion, EA was suggested as the most attractive ingredients for functional food and nutraceuticals because of the high inhibitory activity against 5α-reductase, IL-6 secretion, and lipid peroxidation inhibition.